PERANAN INSPEKTORAT KABUPATENSUMENEP DALAM MENCEGAH DAN MENDETEKSI FRAUD DI DINAS PENDIDIKAN SUMENEP - Astri Furqani; Hafidhah Hafidhah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2015)
In this era, a lot of activities that can not be separated from the practice of cheating or fraud , no exception In the government . Inspektorat Sumenep is the leading institution of internal Local Government in preventing and detecting fraud in the Local Government appropiate Perbup Sumenep No. 29 of 2008 . Dinas Pendidikan Sumenep need attention on the issue . This is due to Dinas Pendidikan Sumenep an agency with the largest number of assets and managing large budgets . These conditions led to the formulation of the problem is How Inspektorat Sumenep role in preventing and detecting fraud in Dinas Pendidikan Sumenep. This study used a qualitative approach in which the focus of this study is Inspektorat role in preventing and detecting fraud at Dinas Pendidikan Sumenep . Primary data obtained by direct interviews with the parties directly related to the determination of the source of research data in a qualitative study using nonprobability sampling . The sampling technique used was purposive sampling . The conclusion of this study, role of the Inspektorat Sumenep in the prevention of fraud in Dinas Pendidikan Sumenep still not maximal . This is due to Inspektorat Sumenep not supervise from the planning / budgeting and not optimal in overseeing and assisting the implementation of the SPIP as an instrument of fraud prevention in Dinas Pendidikan Sumenep . The role of Inspektorat Sumenep in the detection of fraud in Dinas Pendidikan Sumenep done by conducting an audit of financial and asset management in each financial year.Keywords: fraud, government, inspektorat.